Aktivitas Antibakteri Ekstrak Etanol Kulit Nanas (Ananas comosus L. Merr.) terhadap Staphylococcus aureus dan Streptococcus pyogenes: Suatu Penelitian In Vitro - Eliya Mursyida; Frengki Molek Wirajaya; Santi Widiasari (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Skin and soft tissue infections caused by S. aureus and S. pyogenes remain a significant public health concern, particularly in tropical regions. Pineapple peel (Ananas comosus [L.] Merr.), an abundant agricultural by-product, contains several bioactive compounds such as flavonoids, tannins, saponins, and bromelain, which are known for their antibacterial properties. This study aimed to evaluate the antibacterial activity of the ethanol extract of pineapple peel against S. aureus and S. pyogenes. This in vitro experimental study employed a post-test-only control group design. The extract was prepared by maceration using 96% ethanol and diluted with DMSO to obtain final concentrations of 5%, 10%, and 15%. Antibacterial activity was assessed using the well diffusion method on Mueller-Hinton Agar, with 70% ethanol as the positive control and DMSO as the negative control. Inhibition zones were measured after 24 hours of incubation at 37°C. The ethanol extract exhibited inhibitory effects against S. aureus with mean inhibition zone diameters of 4.72±0.88mm (5%), 5.53±0.75mm (10%), and 8.31±1.11mm (15%), and against S. pyogenes with 4.34±0.53mm (5%), 6.20±0.73mm (10%), and 9.29±0.36mm (15%). Statistical analysis using the Kruskal–Wallis test showed significant differences among treatment groups (p < 0.05), confirming that the antibacterial effect was concentration-dependent. In conclusion, the ethanol extract of pineapple peel demonstrated significant antibacterial activity against S. aureus and S. pyogenes, with increasing efficacy at higher concentrations, suggesting its potential as a natural antibacterial agent for future therapeutic or topical applications.